Daya Kreativitas Mahasiswa dalam Mengikuti Lomba Tata Rias Karakter Halloween Tingkat Nasional - Rohmawati, Helmia Cipta; Harwiyati, Enny; Saputri, Nurulisma (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the creativity of students in participating in the National Competition for the Halloween Makeup category. The research subjects were 8 students from 2 private universities, namely 3 students from the Yogyakarta